IL-1β and the Intestinal Epithelial Tight Junction Barrier - Kaminsky, Lauren W.; Al-Sadi, Rana; Ma, Thomas Y. (Frontiers in Immunology, 2021)
The intestinal epithelial tight junction (TJ) barrier controls the paracellular permeation of contents from the intestinal lumen into the intestinal tissue and systemic circulation. A defective intestinal TJ barrier has been implicated as an important pathogenic factor in inflammatory diseases of the gut including Crohn’s disease, ulcerative colitis, necrotizing enterocolitis, and celiac disease. Previous studies have shown that pro-inflammatory cytokines, which are produced during intestinal inflammation, including interleukin-1β (IL-1β), tumor necrosis factor-α, and interferon-γ, have important intestinal TJ barrier-modulating actions. Recent studies have shown that the IL-1β-induced increase in intestinal TJ permeability is an important contributing factor of intestinal inflammation. The IL-1β-induced increase in intestinal TJ permeability is mediated by regulatory signaling pathways and activation of nuclear transcription factor nuclear factor-κB, myosin light chain kinase gene activation, and post-transcriptional occludin gene modulation by microRNA and contributes to the intestinal inflammatory process. In this review, the regulatory role of IL-1β on intestinal TJ barrier, the intracellular mechanisms that mediate the IL-1β modulation of intestinal TJ permeability, and the potential therapeutic targeting of the TJ barrier are discussed.